Rhagadiolus edulis (Cichorieae, Compositae), a replacement name for Lapsana rhagadiolus L. or a name of a new taxon? - Ferrer-Gallego, P. Pablo; Talavera, María (Phytotaxa, 2023)
Rhagadiolus edulis (Cichorieae, Compositae) can be treated either as a replacement name or as the name of a new taxon according to the International Code of Nomenclature for algae, fungi, and plants. Treating it as a replacement name would be nomenclaturally disruptive, whereas treating it as the name of a new taxon, confirmed by an appropriate typification, maintains current usage. Therefore, the nomenclatural type for the name Rhagadiolus edulis is discussed. The name is lectotypified by a specimen preserved in the Gaertner Herbarium at TUB.